The effects of using diesel-citronella fuel blend on the emission and fuel consumption for single-cylinder diesel engine - Erdiwansyah, .; Muhammad, Zaki; Mahidin, .; R., Mamat; Ahmad Fitri, Yusop; Herri, Susanto; Asep, Kadarohman; Fitri, Khoerunnisa; Ratna, Eko Sardjon (Akademi Baru, 2020)
The emissions generated from vehicle engines are one of the problems of global warming worldwide. Conventional oil depletion globally has encouraged various researchers to look for alternative fuel solutions as a substitute for petroleum. Various studies on additive fuels have also studied and most of the fuels have shown perfect results. In this experiment, citronella oil blended into pure diesel fuel to investigate emissions and fuel consumption in a single-cylinder diesel engine. Citronella oil used for diesel fuel blends as much as 0.5%. This test carried out on a single-cylinder engine with three loads (25%, 50% and 75%) and different engine speeds. The results of experiments with diesel-citronella fuel show CO2 emissions lower than pure diesel. Reduction of CO2 emissions from the diesel-citronella mixture for engine loads 25% (0.4%), 50% (0.8%) and 75% (1.9%), respectively. While diesel-citronella fuel blend consumption is higher than pure diesel for each engine load and all speeds tested. Overall diesel-citronella mixed fuel for all tests showed better results compared to pure diesel.